Entrepreneurship and small business : start-up, growth and maturity - Burns, Paul, 1949- (New York : Palgrave Macmillan, 2022)
"Entrepreneurship& Small Business examines the life cycle of firms tracing development from initial start-up, through to growth and maturity. It studies entrepreneurs - what motivates them, how they manage and lead, and how certain defining characteristics they possess can help shape the businesses they run, and the wider environment of entrepreneurship to include family business, and social, civic, philanthropic and corporate enterprises. The book expertly synthesises research foundations and academic studies with real-life practical knowledge and examples. Richly resourced with insights from a wide range of international entrepreneurs and industries, while remaining grounded in academic theory, the text fosters entrepreneurial talent, thinking and skills. Case studies, practice insights, video interviews and discussion scenarios are used to practically demonstrate how concepts are implemented in successful small and growing companies. Clearly structured and accessibly presented throughout, the vitality and expertise of the author make this an engaging and informative read. Burns' text is ideal for undergraduates, MBA students, and students taking specialist postgraduate modules on Entrepreneurship, Enterprise, Small Business Management and New Venture Creation within business and management courses"--
Machine generated contents note: -- PART I: ENTREPRENEURSHIP -- 1. Entrepreneurship: The Social and Business Revolution -- 2. The Economics of Entrepreneurship and Public Policy -- 3. The Entrepreneurial Character -- 4. Discovering a Business Idea -- 5. Researching and Evaluating the Business Idea -- PART II: START-UP -- 6. Start-up: Developing Your Business Model -- 7. Adding Values to the Business Model -- 8. Launching the Business -- 9. Legal Foundations -- 10. Operations and Risk -- 11. Financial Management -- PART III: GROWTH -- 12. Growth: Building the Foundations -- 13. Strategies for Growth -- 14. Financing the Business -- 15. From Business Model to Business Plan -- PART IV: MATURITY -- 16. Maturity: Success and Failure -- 17. Family Business -- 18. From Entrepreneur to Entrepreneurial Leader -- 19. Corporate Entrepreneurship.
Revised edition of the author's Entrepreneurship and small business, 2011.
Includes index.
Keywords: Entrepreneurship -- Study and teaching; Business education; Small business -- Case studies; Entrepreneurship -- Case studies; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Small Business